Characterization of the skin of the lizard Callopistes flavipunctatus of Morrope - Arbulú López, César Augusto (2017)
The present study was performed to characterize skin of C. flavipunctatus lizard of Mórrope, evaluating skin qualities for to tan leather and confections of pledges cooperating for preservation and sustainable exploitation. From January to April 2015 was collected specimens form both sexes evaluating skin weight, process of tan leather and artisanal confection. The results indicate that the lizard studied should be considered as a natural resource and its exploitation should be under sustainability criteria because the species has been listed as “near threatened” by government agencies . It is recommended to continue to investigation of the species to determine whether there is a real effect on the qualities assumed by popular culture, rule out the possibility of filing zoonoses and the possibility to generate protected or exclusion zones to allow the best reproduction species, to avoid predation and repopulate the forest.